What can we learn about twist-2 GPDs through quasi-distributions?. (December 2020) - Bhattacharya, S; Cocuzza, C; Metz, A
Abstract: Studying light-cone PDFs through Euclidean correlators is currently of high interest. In particular, quasi parton distribution functions (quasi-PDFs) have attracted a lot of attention. Quasi-PDFs converge to their respective standard distributions if the hadron momentum goes to infinity. We explore the quasi-distribution approach for twist-2 generalized parton distributions (GPDs) in the conventional diquark spectator model. Our analytical expressions of the quasi-GPDs reduce to their corresponding standard ones in the large-momentum limit, substantiating them to be practical tools to predict features of standard GPDs. We illustrate numerical results of quasi-GPDs and of quasi-PDFs. Our focus is to test how well the quasi distributions agree with their standard counterparts for finite hadron momenta. By discussing the sensitivity of our results to model parameters, we highlight robust features of the quasi-GPDs and quasi-PDFs that one may extract from this model study. We also consider moments of quasi distributions.